2010
DOI: 10.1007/s00464-010-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

The cost effectiveness of elective laparoscopic sigmoid resection for symptomatic diverticular disease: financial outcome of the randomized control Sigma trial

Abstract: Background Direct healthcare costs of patients with symptomatic diverticular disease randomized for either laparoscopic or open elective sigmoid resection are compared. Cost-effectiveness analysis of the laparoscopic approach compared with open sigmoid resections is presented. Methods An economic evaluation of the randomized control Sigma trial was conducted, comparing elective laparoscopic sigmoid resection (LSR) to open sigmoid resection (OSR) in patients with symptomatic diverticulitis. Prospective registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Lower costs for hospitalization (2983 vs. 3598 €), blood products (87 vs. 240 €), paramedical services (157 vs. 278 €), and emergency attendance (72 vs. 115 €) in the LSR group partially compensated these increased operation costs. Taken together, the authors concluded that total healthcare costs for laparoscopic and open sigmoid resection were similar and that patients should, therefore, be preferentially treated laparoscopically given its other advantages [18] (level of evidence: 2a).…”
Section: Minimally Invasive Surgery For Elective Treatment Of Divertimentioning
confidence: 96%
“…Lower costs for hospitalization (2983 vs. 3598 €), blood products (87 vs. 240 €), paramedical services (157 vs. 278 €), and emergency attendance (72 vs. 115 €) in the LSR group partially compensated these increased operation costs. Taken together, the authors concluded that total healthcare costs for laparoscopic and open sigmoid resection were similar and that patients should, therefore, be preferentially treated laparoscopically given its other advantages [18] (level of evidence: 2a).…”
Section: Minimally Invasive Surgery For Elective Treatment Of Divertimentioning
confidence: 96%
“…Laparoscopy was associated with less pain and higher quality of life scores in the short term, while 6-month follow-up showed no difference in late complications or recurrence. 49 In a financial analysis, the cost of a 1% complication reduction attributable to laparoscopy was a mere €31, making laparoscopic approach a bargain for patients and hospitals. 49 A subsequent study in 2010 with similar design showed no difference in complication rates between laparoscopic (13.5%) and open (9%) groups, reduced perception of pain in laparoscopy and similar quality-of-life scores aside from cosmesis.…”
Section: Elective Resection For Diverticulitismentioning
confidence: 99%
“…49 In a financial analysis, the cost of a 1% complication reduction attributable to laparoscopy was a mere €31, making laparoscopic approach a bargain for patients and hospitals. 49 A subsequent study in 2010 with similar design showed no difference in complication rates between laparoscopic (13.5%) and open (9%) groups, reduced perception of pain in laparoscopy and similar quality-of-life scores aside from cosmesis. 50,51 Patients undergoing conversion experienced worsened outcomes, making patient selection an important factor for better outcomes.…”
Section: Elective Resection For Diverticulitismentioning
confidence: 99%
“…Laparoscopic resection for both symptomatic and perforated diverticulitis have been shown to be as safe and effective as conventional open techniques [41,42] and the results of a cost-effectiveness analysis of a laparoscopic approach compared with open sigmoid resection were similar [43,44]. …”
Section: Development In Managementmentioning
confidence: 99%